Marker-assisted pyramiding of southern leaf blight resistance QTLs qSLB3.1 and qSLB8.1 in maize (Zea mays) - KAUR, PRABHMEET; KAUR, GURWINDER; KYUM, MOHAMMED; KAUR, SHABNEEK; BAINS, SUTEJ; SHARMA, PRITI; KAUR, HARLEEN; SANDHU, SURINDER K; VIKAL, YOGESH (The Indian Journal of Agricultural Sciences, 2022)
Southern leaf blight (SLB) is one of the major diseases that cause substantial yield losses in maize (Zea mays L.) worldwide. Stacking broad-spectrum resistance genes/QTLs into prevalent cultivars is the prerequisite for durable disease resistance breeding programme. Therefore, a study was carried at the research farm and molecular biology laboratory of School of Agricultural Biotechnology, Punjab Agricultural University, Ludhiana, Punjab during 2017–21 to introgress SLB resistance QTLs from two donors, viz. CM139 (qSLB3.1) and LM5 (qSLB8.1) into CM140 inbred using marker-assisted backcross breeding (MABB). Crosses were made between CM139 × CM140 and LM5 × CM140 to generate two separate F1s. Each F1 was backcrossed twice to generate BC2F1 progenies. Foreground selection was performed at each step using linked flanking markers to each QTL and also evaluated for SLB resistance. The selected heterozygous BC2F1 plants from each cross were inter-crossed to combine qSLB3.1 and qSLB8.1 in the same genetic background. The F2 population was also evaluated phenotypically for SLB resistance and other morphological traits. A total of 18 plants were obtained having both the QTLs with homozygous donor alleles. The F2 plants having both QTLs and singly in the homozygous state were advanced to generate F3 progenies. The pyramided lines exhibited 29% lesser disease severity than the lines with either QTL. The present results indicated that additive effects of the QTLs for SLB resistance played an important role among these lines. To our best knowledge, this is the first report for the pyramiding of QTLs associated with SLB resistance. The pyramided lines would serve as potential donors in maize breeding programs.